Penggunaan beberapa level sorgum (Sorghum bicolor l.) dalam ransum terhadap penampilan ayam broiler CP 707 - Yonatan Tanggu; I Gede Sutapa; Ni Ketut Etty Suwitari (Fakultas Pertanian, Universitas Warmadewa, 2018)
Feed is one important factor in determining the performance of poultry production, especially broiler. Increasing the quality of feed can be done by using sorghum seeds in the feed ration is supplement (substitutions) to corn, because the nutritional value is not different from corn is cheap and does not compete with human needs, easy to obtain and good quality. Sorghum (Sorghum bicolor L.) is a cereal crop that is potential for cultivation and development, especially in marginal and dry areas of Indonesia, can be used as an alternative feed for broiler. The purpose of this research is to determine the effect of sorghum as a substitution of corn on the performance of broiler. This research used Completely Randomized Design (CRD) with 5 treatments and 3 replications with each replication consisted of 3 broiler CP 707, so the number of broiler in use as many as 45 broiler. The treatment was as follows: R0 = Control ration without sorghum addition, R1 =7% sorghum, R2 = 14% sorghum, R3 =21% sorghum, R4 =28% sorghum. The parameters observed were initial weight, weight gain, final weight, feed intake and feed conversion ratio. The data obtained were analysis with analysis of variance. The result of this research showed that the ration of sorghum added gave significant difference (P0,05) to the ration consumption while the feed conversion ratio had the effect (P